Variations in Rectal Volumes and Dosimetry Values Including NTCP due to Interfractional Variability When Administering 2D-Based IG-IMRT for Prostate Cancer. (14th July 2014) - Hanada, Takashi; Shiraishi, Yutaka; Ohashi, Toshio; Fukada, Junichi; Tanaka, Tomoki; Yorozu, Atsunori; Shigematsu, Naoyuki
Abstract : We estimated variations in rectal volumes and dosimetry values including NTCP with interfractional motion during prostate IG-IMRT. Rectal volumes, DVH parameters, and NTCPs of 20 patients were analyzed. For this patient population, the median (range) volume on the initial plan for the rectum was 45.6 cc (31.3–82.0), showing on-treatment spread around the initial prediction based on the initial plan. DVH parameters of on-treatment CBCT analyses showed systematic regularity shift from the prediction based on the initial plan. Using the Lyman-Kutcher-Burman model, NTCPs of predicted late rectal bleeding toxicity of rectal grade ≥ 2 (RTOG) and the QUANTEC update rectal toxicity for the prediction based on the initial plan were 0.09% (0.02–0.24) and 0.02% (0.00–0.07), respectively, with NTCPs from on-treatment CBCT analyses being 0.35% (0.01–6.16) and 0.12% (0.00–4.11), respectively. Using the relative seriality model, for grade ≥ 2 bleeding rectal toxicity, NTCP of the prediction based on the initial plan was 0.64% (0.15–1.22) versus 1.48% (0.18–7.66) for on-treatment CBCT analysis. Interfraction variations in rectal volumes occur in all patients due to physiological changes. Thus, rectal assessment during 2D-based IG-IMRT using NTCP models has the potential to provide useful and practical dosimetric verification.